2001
DOI: 10.1055/s-2001-15452
|View full text |Cite
|
Sign up to set email alerts
|

St. John's Wort Extract Ze 117 (Hypericum perforatum) Inhibits Norepinephrine and Serotonin Uptake into Rat Brain Slices and Reduces β-Adrenoceptor Numbers on Cultured Rat Brain Cells

Abstract: Despite almost forty years of widespread use, the mode of action of antidepressant drugs is still largely unknown. There is agreement that these drugs interact with central neurotransmission. Common findings are acute inhibitory actions on reuptake mechanisms for norepinephrine (NE) and for serotonin (5-HT) at presynaptic axons and chronic adaptive effects on neurotransmitter receptors on postsynaptic membranes. In particular, beta-adrenoceptor downregulation has been observed after chronic treatment with most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…Similar drug dilution cases were observed with birth control pills and coronary transplant antirejection medications (5). Recent reports indicate some metabolites other than HyH as the cause of these unwanted drug interactions in St. John's wort extracts (5,9). Thus, the purification and bioprocessing of HyH, the antidepressant compound in St. John's wort, may be of medical importance in the treatment of depression, and in avoiding the side effects associated with this herbal remedy.…”
mentioning
confidence: 62%
“…Similar drug dilution cases were observed with birth control pills and coronary transplant antirejection medications (5). Recent reports indicate some metabolites other than HyH as the cause of these unwanted drug interactions in St. John's wort extracts (5,9). Thus, the purification and bioprocessing of HyH, the antidepressant compound in St. John's wort, may be of medical importance in the treatment of depression, and in avoiding the side effects associated with this herbal remedy.…”
mentioning
confidence: 62%
“…Importantly, the onset of down-regulation and clinical effectiveness requires 10 -20 days of antidepressant treatment (43). We have previously shown that in cultured C6 cells chronic exposure to DMI results in a progressive reduction in ␤1AR surface receptor density within similar periods of time (10). C6 cells thus provide a valid model system to examine potential mechanisms that might underlie the clinical and experimental long term observations.…”
Section: Discussionmentioning
confidence: 99%
“…in cultured rat C6 glioblastoma cells (9,10). Thus, ␤AR down-regulation may directly result from postsynaptic actions of the antidepressants.…”
mentioning
confidence: 99%
“…In der Studie von Kientsch et al [42] wurde außerdem eine b-down-Regulation in Astrozytenzellen der Ratte nach Gabe von ZE 117 nachgewiesen, die der b-down-Regulation nach Gabe von Desipramin vergleichbar war. Auch Müller et al [58] fanden eine Downregulation von b-Rezeptoren im Bereich des frontalen Kortex nach chronischer oraler Gabe von Hyperikumextrakten.…”
Section: Downregulation Der B-rezeptorenunclassified